A pilot study of improved psychological distress with art therapy in patients with cancer undergoing chemotherapy - E. B. Elimimian; L. Elson; E. Stone; R. S. Butler; M. Doll; S. Roshon; C. Kondaki; A. Padgett; Z. A. Nahleh (BMC Cancer, 2020)
Abstract Background Art therapy may improve the physical, mental, and emotional wellbeing of individuals for a variety of purposes. It remains understudied and underutilized in cancer care. We sought to determine the ability of a pilot art therapy program to improve the physical, mental, and emotional well-being of cancer patients. Methods Chemotherapy-recipients, age 18 years and older, diagnosed with any type or stage of cancer, were considered eligible to participate in this single arm, pilot study, using four visual analog scales (VAS) with visually-similar, 0–10 scale (10 being worst) thermometers assessing: 1) pain, 2) emotional distress, 3) depression, and 4) anxiety. Participants were asked to complete all 4 metrics, pre-treatment, post-treatment, and at 48–72 h follow-up, after an hour-long art therapy session. Primary endpoints included post-intervention changes from baseline in the 4 VAS metrics. Results Through a reasonable pilot sample (n = 50), 44% had breast cancer, 22% gastrointestinal cancers, 18% hematological malignancies, and 20% had other malignancies. A decrease in all VAS measures was noted immediately post-treatment but remained low only for pain and depression, not for emotional distress and anxiety upon follow up. There was a significant difference between the depression VAS scores of Hispanics (32%) compared to non-Hispanics (56%) (p = 0.009) at baseline. However, compared to non-Hispanics, Hispanics exhibited higher levels of depression after art therapy (P = 0.03) and during the follow-up intervals (p = 0.047). Conclusion Art therapy improved the emotional distress, depression, anxiety and pain among all cancer patients, at all time points. While depression scores were higher pre-intervention for Hispanic patients, Hispanic patients were noted to derive a greater improvement in depression scores from art therapy over time, compared to non-Hispanics patients. Discovering simple, effective, therapeutic interventions, to aid in distress relief in cancer patients, is important for ensuring clinical efficacy of treatment and improved quality of life.